The Stronger Impact of National Culture over Organizational Culture on Supply Chain Operations - Roy Vincentius Pratikno (Universitas Pelita Harapan, 2018)
The proponents of national culture have a strong belief that national culture has an impact on the performance of a firm. They also believe that national culture influences team work and the ability to innovate. They consider the impact of national culture on behavior and relationships to be longer lasting than cultural influences that tend to diminish as a company changes. On the other hand, the supporters of organizational culture have a strong conviction that well-defined and widely used organizational practices throughout the organization will help an organization become excellent and capable of achieving high levels of performance. Both the partisans of organizational culture and the supporters of national culture have their own reasons as to why each side is more impactful when compared to the other. This paper attempts to answer which side has a stronger impact by reviewing the literature on the effect of national culture or organizational culture on the supply chain operations of MNCs in Japan and the US. It appears that national culture is more impactful than organizational culture when it comes to supply chain operations.BAHASA INDONESIA ABSTRAK: Para pendukung budaya nasional memiliki keyakinan kuat bahwa budaya nasional berdampak pada kinerja perusahaan, mereka juga percaya bahwa budaya nasional mempengaruhi kerja tim, kemampuan untuk berinovasi dan mereka mempertimbangkan dampak budaya nasional terhadap perilaku, hubungan yang berkelanjutan setidaknya itu akan bertahan lebih lama dibandingkan dengan pengaruh budaya organisasi yang cenderung berkurang seiring perubahan perusahaan. Di sisi lain, para pendukung budaya organisasi memiliki keyakinan yang kuat bahwa melalui praktik organisasi yang didefinisikan dengan baik dan banyak digunakan di seluruh organisasi akan membantu organisasi untuk menjadi organisasi yang sangat baik yang mampu mencapai kinerja organisasi yang sangat baik. Baik pendukung budaya organisasi maupun pendukung budaya nasional memiliki alasan sendiri mengapa masing-masing pihak lebih berdampak dibandingkan dengan pihak lain. Makalah ini mencoba untuk menjawab sisi mana yang memang memiliki dampak yang lebih kuat dengan meninjau beberapa literatur tentang pengaruh budaya nasional atau budaya organisasi pada operasi rantai pasokan MNC di Jepang dan AS. Tampaknya budaya nasional lebih berdampak dibandingkan dengan budaya organisasi ketika datang ke operasi rantai pasokan.